Processing of Ceramic Matrix Composites by RMI Technique and Characterization of the (Al, Si, B4C) Components of Composites - R. Arivumani; C. Ramkumar; D. Rajasekaran; M. Palanisamy; J. Sridharanidharan; N. Dhanaraj; S. Deenadhayalan (Archives of Metallurgy and Materials, 2025)
To attain the goal of receiving the well toughened ceramic matrix composite material for radioactive jackets to protect from nuclear radioactivity for commercial and defense applications. This research task is initiated to prepare the composites by preparing the Al-Si alloy at different propositions and infiltrate the alloy into the B4C pellets at different temperatures. This task dealt with the methodology of reactive melt infiltration (RMI) technique and processing of ceramic matrix composites in lightweight. Moreover, it registered the phenomenon and factors influencing the infiltration process and characterization of constituents of the ceramic matrix infiltrated composites. Fine particles of 10 μm boron carbide powder (B4C) was characterized by determining the free carbon content and thermal behavior experiments. By the addition of binder, the densification of porous B4C green preforms and its pressing efficiency were analyzed. Four sets of Si-Al alloys were produced with various combinations and smelting parameters; and were investigated its property through XRD/EDS tests and SEM images. Nominal 50% porosity B4C preforms were infiltrated by various proportions of hypereutectic Si-Al alloys at various batches through pressureless reactive melt infiltration process under inert argon atmosphere with different infiltration temperatures and infiltration duration. The poor infiltration, partial infiltration, changes in physical aspect, wetting phenomena were also discussed.